1997
DOI: 10.1111/j.1600-051x.1997.tb01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth mobility and periodontal Disease

Abstract: Tooth mobility (TM) is an important feature of periodontal disease. This is evidenced by the large number of devices and methods of TM assessment that have been developed and tested. TM had been considered and investigated as an indirect measure of the functional condition of the periodontium as well as possible aggravating co-factor for periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 55 publications
4
43
0
1
Order By: Relevance
“…Ferrier et al showed that the increased movement of the tooth in the initial phase of force application results from a change in fluid content, while a more gradual increase in displacement over a considerably greater force range results from stress being taken up by the collagen fibers [3]. This first phase of tooth displacement depends on the conditions of periodontal soft tissues and relates to vascular components of the periodontium [4,11,19,24]. Wills et al stated that the part played by the fluid system in the periodontium, mainly the blood, account for 30% of the displacement of the tooth, while another 10% may be attributable to extracellular fluid [27].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ferrier et al showed that the increased movement of the tooth in the initial phase of force application results from a change in fluid content, while a more gradual increase in displacement over a considerably greater force range results from stress being taken up by the collagen fibers [3]. This first phase of tooth displacement depends on the conditions of periodontal soft tissues and relates to vascular components of the periodontium [4,11,19,24]. Wills et al stated that the part played by the fluid system in the periodontium, mainly the blood, account for 30% of the displacement of the tooth, while another 10% may be attributable to extracellular fluid [27].…”
Section: Discussionmentioning
confidence: 96%
“…The value of the component with index 2 is 1 for drug administered and 0 for drug not administered. Components (1,3,4) are discarded in this demonstration. Index 5 corresponds to the baseline.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Lindhe who conducted the study to see the effects of trauma from occlusion and the periodontal status if the bacterial plaque factor was not included. The study concluded that there was no difference in alveolar bone loss between the 2 control and the test groups [16].…”
Section: Advances In Health Science Research Volumementioning
confidence: 93%
“…This flexibility can be observed as tooth mobility, even in healthy periodontal tissue (19,20), and the degree of tooth mobility is one way to identify periodontal disease (21). Traditionally, Miller's technique (2) has been used for this purpose, because of its simplicity and practicality in clinical settings.…”
Section: Discussionmentioning
confidence: 99%